Gender and Entrepreneurship: Motivational Factors for Women Entrepreneurs in India - Shunmugasundaram, V.; Nupur, Nupur (International Journal of Economics and Financial Issues, 2023)
The goal of the present research is to examine whether demographic variables can differentiate among the motivational factors of women entrepreneurs in India. The findings of Ozsunger, 2019 are elongated in the current study. Data was collected from the business owners of small, medium, and micro enterprises from the Haryana state of India. Respondents were asked questions on four dimensions of motivational factors i.e., push, pull, balanced and emotional factors that influence women-owned enterprises. The study used survey research. The findings of the paper show that training, experience, medium-sized enterprises, and assistance from financial institutions can differentiate the motivational factors. The study collected data from five districts of Haryana, and diversified data could have been used. A mixed methods approach could have been used instead of a quantitative approach.